Crafting Future Memories: Reflections on a Female Carpentry Training Project in Lagos - Aluko-Kpotie, Bukola (Qualitative Studies, 2023)
M yths of gendered labour and specifically the masculinisation of certain forms of artisanship are both steeped in Victorian colonial ideals of female respectability that serve to exclude unemployed, educated women from market relevant, lucrative jobs in carpentry trades, in the city of Lagos, West Africa. These hist orically situated dynamics of social exclusion expose an increasing number of educated women to poverty in one of Africa's primary economic hubs. Utilising the linguistic devices of rich descriptions and first person accounts in this reflective paper, and drawing data from culturally grounded ethnographic research on a female carpentry training project in the city, I examine how the communities which emerged from the project negotiate socio economic, familial, and historical constraints in an effort to buil d new, inclusive training pathways and craft alternative future narratives of gendered labour practices in Lagos. Keywords